Development of Novel Nucleic acid-based Reagents for Specific Allergen Detection - Schäfer, Laura; Justus Liebig University Giessen (My University, 2025)
Food allergies remain a significant global health concern, affecting up to 10% of the global population, with an upward trend. The most effective method of preventing an allergic reaction is the strict avoidance of allergens. The basic prerequisite for avoiding contact with food allergens is knowledge of the presence of allergens in food. According to European Regulation No. 1169/2011, allergens must be labelled if they are used as an ingredient in food. In contrast, there is currently no legal regulation for unintentional ‘hidden’ allergens that have been transferred, for example from an allergen-containing food to an ‘allergen-free’ food during the production. Food manufacturers have the option of applying a ‘precautionary allergen labelling’ (PAL) claim, such as ‘may contain traces of (...)’, to raise awareness of potential allergen risks. However, this is not subject to any regulatory defined threshold values. Detection methods for allergens are therefore essential to ensure unambiguous allergen labelling on foods in the case of allergen ingredients and thus give consumers the opportunity to strictly avoid allergenic foods. Furthermore, sensitive and specific detection methods can be used to detect minor amounts of so-called ‘hidden’ allergens and thus contribute to the useful and reliable use of PAL claims. In the field of medicinal products, detection methods can be crucial in the assessment of the quality of diagnostic and therapeutic allergen preparations with regard to relevant allergen components. They can also be used to analyze, for example, study material used in double-blind, placebo-controlled food studies to verify allergen-containing and allergen-free (placebo) samples. Animal-derived antibodies, especially polyclonal antisera, play an important role in in vitro diagnostic detection systems, but can lead to quality problems due to natural variations and thus to inconsistencies from batch to batch. Animal testing is also associated with ethical concerns. In accordance with the 3R principle (Replacement, Reduction, Refinement) and the requirements of European Directive 2010/63/EU, procedures involving living animals should be replaced as soon as scientific alternatives are available. In order to meet these requirements, the aim of this research project was to develop nucleic acid-based alternatives to replace antibodies in allergen detection methods. Two approaches were pursued. Firstly, the potential of single stranded DNA aptamers, which can bind a large number of molecules due to their sequence-dependent tertiary structure, was investigated. The SELEX process (Systematic Evolution of Ligands by Exponential Enrichment) was applied to generate specific aptamers, thereby achieving a selective enrichment of aptamers against the peanut allergen Ara h 1 (7S globulin). Subsequent next generation sequencing (NGS) was used to identify the underlying nucleic acid sequences. Additionally, the aptamers were characterized using surface plasmon resonance (SPR) with regard to their dissociation constants (KD) and possible cross-reactivities. Three aptamers (LS_Arah1_367, LS_Arah1_535, LS_Arah1_725) showed the strongest binding to the target protein Ara h 1 with KD values between 88 and 988 nM, and no measurable cross-reactivity to the other peanut allergens Ara h 2, 3 and 6. The most suitable aptamers were then successfully applied in different assays such as an ELISA-like method for the detection of Ara h 1. By using the aptamer LS_Arah1_367 in an indirect assay, a sensitivity of 10 ng/mL Ara h 1 was achieved, which is comparable to published antibody-based ELISA systems. In addition, peanut flours and peanut-containing cookies as an example of a thermally processed food matrix were successfully analyzed, so that antibody-free methods for the detection of Ara h 1 were developed that meet the objectives of the European Directive 2010/63/EU. The second approach involved the development of a LAMP primer set targeting the hazelnut-specific multicopy gene internal transcribed spacer 2 (ITS2). After in silico generation of specific primers with subsequent empirical testing, a specific LAMP-based method was developed that can detect at or below 10 mg hazelnut per kg of food and showed no cross-reactivity to 22 other foods. In combination with a recently developed, efficient DNA extraction protocol and colorimetric visualization of results, the method can act as a fast and simple screening tool (1 min sample lysis, 20 min DNA purification, 45 min amplification and visual detection). Validation work has confirmed its suitability for the specific and sensitive detection of hazelnut in complex food matrices. The developed LAMP method thus allows the evaluation of the presence of hazelnut as an allergenic food and promotes risk-based, preventive labelling of hazelnut in compound foods. This method can also be used for the general authentication of hazelnut through the indirect detection of a hazelnut-specific DNA region, for example in standardized, clinical-diagnostic and future therapeutic approaches. Both the development of aptamer-based methods and LAMP-based methods show the great potential of nucleic acid-based reagents as direct (aptamers) and indirect (LAMP primers) alternatives to antibodies (Figure 1). In contrast to polyclonal antibodies, nucleic acids can be chemically synthesized in a reproducible manner, so that the risk of batch-dependent variations is reduced to a minimum and standardization is possible. In addition, no animal testing is required for the synthesis of aptamers or LAMP primers, thus eliminating ethical concerns (neither for the animals nor for the people carrying out the animal testing).
Keywords: food allergy; aptamer; Loop-mediated isothermal amplification; ddc:540; ddc:500